Strategi Penanggulangan Kelemahan Terhadap Ancaman Keamanan Pada Jaringan Wireless - Wadly, Fachrid; Septian, Rio; Ramadhan, Zuhri (Jurnal Nasional Teknologi Komputer, 2023)
The use of wireless-based technology devices at this time is so much, good used for voice and data communications. Because wireless technology utilizes frequency high to deliver a communication, then the vulnerability to security is also higher compared to other communication technologies. Various security measures can be taken through communication devices used by users and by operators who provide services communication. Weaknesses of wireless networks in general can be divided into 2 types, namely weaknesses on the configuration and weakness on the type of encryption used. Broadly speaking, the gap on wireless network spans over four layers where the four layers actually are is the process of occurrence of data communication on wireless media. The four layers are layers physical layer, network layer, user layer, and application layer. The security handling models that occur in each layer of wireless technology can be done, among others, by: hide SSID, make use of WEP keys, WPA-PSK or WPA2-PSK, facility implementation, MAC filtering, installation of captive portal infrastructure.